Analisis Potensi dan Status Kerusakan Tanah pada Lahan Kering Berbasis Sistem Informasi Geografis di Kecamatan Baturiti, Kabupaten Tabanan, Provinsi Bali - KRISNAYANTI, NI KADEK ARY; TRIGUNASIH, NI MADE; NARKA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 13 No 1 (2023)DO - 10.24843/AJoAS.2023.v13.i01.p11, 2023)
Analysis of Soil Degradation Potential and Status in Agricultural Dry Land Based on Geographic Information Systems in Baturiti Sub-District . Biomass production activities that do not pay attention to conservation principles can cause soil degradation. This will reduce the productivity of natural resources, forestry and agriculture. The purpose of this research are to determine the potential, status, and distribution of soil degradation on dry land farming in Baturiti Sub-district. The method used on this research is a comparative descriptive method. Based on overlay of land use map, slope map, and soil type map using geographic information system, 9 homogenous land units were obtained. The land use observed was mixed gardens and dry fields with field observations of surface rocks and solum depth. Samples were analyzed in the laboratory to determine bulk density, total porosity, texture, permeability, pH, DHL, and microbial count. Determination of degradation status based on standard criteria of soil degradation. The results showed three classes of potential soil degradation, namely the potential for mild soil degradation at Perean Tengah, medium soil degradation potential at Baturiti, Antapan, Luwus, Bangli, Angseri, Candikuning, and the high potential soil degradation at Antapan. The soil degradation status was found lightly damaged status with permeability limiting factors at Baturiti and partially Antapan, with limiting factors for permeability and composition of fractions at Candikuning and partially Antapan, limiting factors for permeability and porosity total at Perean Tengah.